(untitled) (Global Journals of Research in Engineering, 2013)
This paper focuses on the investigation study of Total Harmonic Distortion (THD) in a sevenlevel Flying Capacitor Multilevel Inverter (FCMLI) with / without closed-loop feedback schemes. For that, a closed-loop model is designed for the existing FCMLI through this paper. Conventionally full bridge and half bridge inverter configurations are used for certain applications where DC-AC conversion is needed. But the main drawbacks of these inverters are high harmonic content and used only for limited power applications. In order to overcome this, a novel approach called closed-loop FCMLI will be proposed, which significantly increases the level number of the output waveform and thereby dramatically reduces the low-order harmonics and THD. The proposed system consists of a DC#x2013;DC power converter and a DC#x2013;AC multilevel inverter. In order to achieve low cost, easy control, high efficiency, and high reliability, a capacitor clamped DC#x2013;DC boost converter using minimal devices is introduced to interface the lowvoltage Photovoltaic (PV) module.